The Demand of Change in Teaching and Learning: What are the teachers' reactions? - Christina Andin, Nur Qistina Abdullah; Jeannet, Stephen; Abdul Said, Ambotang; Yusri, Kamin; Rosmiza, M.; Rohana, Hamzah; Daniel, Ugih (SPED sp.z o.o., 2022)
Educational reform has become a top priority for many countries due to the rapid changes in the globalization era. Hence, various educational transformations related to teaching and learning have been introduced for improving the quality of education. However, the implementation of new policies often strays from the original goals. In the context of education, the challenges of educational reform stem from policymakers not considering the impact of change on all interdependent components of the school ecosystem. One of the most important components of the school ecosystem is the teacher. So, this study aims to explore the reactions of teachers to the changes in teaching and learning that they have gone through. The reactions consist of cognitive, affective, and behavioral elements. This study employed a qualitative approach with semi-structured interviews as the research instrument. The study involved 12 secondary school teachers from the West Coast Zone of Sabah, Malaysia. Data analysis using thematic methods. The results show that there are four dimensions of teachers' reactions, namely Support Change, Dilemma, Indifferent, and Reject Change. The results of this study provide benefits to stakeholders in policy formulation related to teaching and learning in the classroom.